JENIS DAN SEKS-RASIO UDANG BARONG (Panulirus spp.) DI KAWASAN PANTAI GUNUNG KIDUL, YOGYAKARTA - Sukiman Wirosaputro (Universitas Gadjah Mada, 1996)
Activity researched for lobster in coastal area Gunungkidul Yogyakarta began November, 1995 to Februari, 1996. Number of lobsters to identify were 3,755 head for species and 1,525 head for sex-ratio. Number of species were 6kinds, there were : Panulirus pencillatus (56.48%), P. homarus (30.38%), P. longipes (6.73%), P. ornatus (5.40%), P, versicolor (0.95%), P. polyphagus (0.06%). General sex-ratio between male:female = 1.83:1.00. number of female carrying eggs 3.40% and not carrying eggs 32.54%. Sex-ratio for each species between male:female for P. penicillatus, P. homarus, P. longipes, P. ornatus, P. versicolor, P. polyphagus, were = 1.83:1.00 ; 1.71:1.00 ; 2.20:1.00 ; 0.97:1.00 ; 2.40:1.00 ; 1.00:0.00 respectively.